Factors Influencing the Acceptance of the Innovative for the Government Savings Bank’s Face-recognition-based ATM Transactions in Bangkok - Patikanang, Chutima; Rakbumrung, Wilailuk (Journal of Innovation and Management, 2020)
The purpose of this study was to examine the demographic characteristics and study the technological factors that influence the acceptance of the innovative for the Government Savings Bank’s face-recognition-based ATM transactions in Bangkok. The research was conducted in a quantitative design. The sample of the study were comprised of 400 customers of the Bank’s branches in Bangkok. Selected by the multi-stage, Regarding the research instrument, questionnaire was used. The data were collected and analyzed by means of descriptive statistics: frequency, percentage, average, and standard deviation and of inferential statistics: ANOVA and multiple regression analysis. Research Findings are as follows: (1) the demographic characteristics that influence the acceptance of the innovative for the Government Savings Bank’s face-recognition-based ATM transactions in Bangkok, the authors have considered gender, age, education, average income, and current profession.The participating customers with different ages, income, and professions have been disclosed to have a different degree to accept the innovative for the Government Savings Bank’s face-recognition-based ATM transactions in Bangkok, which is at a level of .05. For the other factors, the difference is not found, and (2) the factors influencing the acceptance of the innovative for the Government Savings Bank’s face-recognition-based ATM transactions in Bangkok have been reported 69.8% of prediction accuracy. Having tested each independent and dependent variable singly, it has been revealed that the behavioral intention to use, attitude toward using, perceived ease of use as well as perceived usefulness could have some influence on the acceptance of the innovative for the Government Savings Bank’s face-recognition-based ATM transactions in Bangkok, significantly at a statistical level of .05.